Western perspectives on Chinese higher education : a model for cross-cultural inquiry - Liu, Xiuwu R., 1957- (Madison, N.J. : Fairleigh Dickinson University Press ; London ; Cranbury, NJ : Associated University Presses, 1996)
This book argues that constructivism and realism, two prominent theories of scholarly inquiry in a variety of fields, both have their strengths and weaknesses as descriptive models of how research is conducted and written up and as normative models for improving inquiry.
Drawing on the two theories' strengths while avoiding their weaknesses, the book proposes realist constructivism as a general epistemic model for one area of inquiry - cross-cultural studies, defined as studies involving scholars from one society or culture studying another. The model has a descriptive and a normative dimension. Descriptively, realist constructivism maintains that a scholarly study of another society does reveal and is constrained by the studied society's social reality while being thoroughly shaped by factors involving the scholar and his society, whereas normatively it urges that a cross-cultural study should reveal and be constrained by the studied society's relevant social reality while being thoroughly shaped by a host of factors involving the scholar and his society.
1. Introduction: What is Realist Constructivism? -- 2. Approaches, Statements, and Assumptions -- 3. Emphases and Silences -- 4. Translating Terms -- 5. Points of View -- 6. Evaluation -- 7. Methodological Summary -- 8. Concluding Remarks.
Includes bibliographical references (p. 159-183) and index.
Keywords: Education, Higher -- China -- Cross-cultural studies